Two levels vs. one level of phallopexy in the treatment of concealed penis in patients in pediatric age group - Elrouby, Ahmed; Saad, Israa; Kotb, Mostafa (Frontiers in Pediatrics, 2023)
Abstract Introduction: Concealed penis which is the congenital type of buried penis is a condition in which a normal size penis is totally or partially hidden by pubic, scrotal, or thigh skin. Several procedures had been described for its correction including phallopexy i.e. fixation of penile Buck’s fascia to the sub-dermis. Aim of the work: Our work aimed to study the difference in the outcome of performing phallopexy at one level and two levels. Material & Methods: Our study included 180 uncircumcised patients having a concealed penis while having an average length of outstretched penis. These patients were divided into two groups; the first one was treated with one level of phallopexy at 3 and 9 o’clock points, while the second group was treated by the same procedure in addition to another level of stitches at the mid-penile level. The follow-up was carried out for one post-operative year regarding penile skin edema, infection, congestion, necrosis, and/or re-retraction. Results: the overall success rate was 96.1% of a normally-looking penis without post-operative re-retraction. Re-retraction developed in 2 patients (2.2%) of those who had one level phallopexy and in 5 patients (5.6%) of those who had two-level phallopexy without statistical significance (FEp=0.444). Penile skin edema developed in 76 patients (42.2%) being significantly lower in patients with lower body weight (p=0.030*). Conclusion: Phallopexy could be done safely in the case of the concealed penis with satisfactory results and minimal complications whether at one or two levels with a similar outcome. So we recommend the easier one-level phallopexy in the treatment of such conditions with satisfactory results